A high-power factor permanent magnet vernier motor for direct drive application - Guo, Feifan (Nanyang Technological University, 2023)
This dissertation designs a Permanent Magnet Vernier Motor for direct drive application on electric vehicle with given design requirement. Surface mounted radial excitation permanent magnet is applied on the outer rotor for initial design. The critical issue, low power factor, restricts the current can be injected into the motor. Output torque is very low. New design swaps the radial excitation surface mounted permanent magnet with Halbach array permanent magnet. Furthermore, optimizations about number of turns, magnet height and split teeth distance are made. The power factor and torque density are much better than the initial design. Finally, the PMVM torque density can reach 28.76 ∙ / while the power factor remains above 0.8. Further study about the optimization of other parameters will be conducted and prototype can be made to do experimental validation in the future.